Molecular Docking Study of Caffeic Acid as Acetylcholinesterase Inhibitor - Wira Waskitha, Stephanus Satria; Istyastono, Enade Perdana; Octa Riswanto , Florentinus Dika (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2023)
Abstract: Acetylcholinesterase (AChE) receptor is a receptor that has been widely used as a potential drug target for Alzheimer's disease. Caffeic acid is a phenolic compound that had been experimentally proven to be an inhibitor of AChE. In this study, 100 molecular docking simulations were performed to study the interaction of caffeic acid in inhibiting AChE. The molecular docking simulations were performed using YASARA software with an in-house developed plug-in. Redocking results showed that there were 99 out of 100 docking poses had an RMSD value of ≤ 2.000 Å, which indicated that the molecular docking procedure could be used for further processes. The molecular docking of caffeic acid showed that all docking poses had an RMSD value of ≤ 2.000 Å relative to the best pose of the first simulation, revealing that there was only one dominant docking pose in the AChE active site. Caffeic acid interacted favorably in the AChE active site with binding energy of about -8.022 kcal/mol. Its interactions were stabilized by hydrophobic and pi-anion interactions, in which some of the interactions resemble the same interaction of the native ligand. Keywords: Acetylcholinesterase, Alzheimer's disease, caffeic acid, molecular docking